Exploring the relationship between the water-energy-food nexus and livelihoods at the local scale: a case study focussed on a low-income residential area in Velddrif, South Africa - Price, Penelope (Department of Environmental and Geographical Science, 2025)
The water-energy-food nexus (WEF nexus) has primarily been applied to addressing WEF security at large spatial scales in response to resource scarcity concerns. In contrast, WEF security at local levels, particularly amongst the poor, has received little attention. This thesis addresses this gap by exploring the application of the WEF nexus at the local level through a case study of a low-income residential area in the small urban fishing town of Velddrif on the west coast of South Africa. The primary empirical focus of the study is the household where availability, access, and affordability of WEF resources, as well as the linkages to livelihood options, are explored through a household survey. This is complemented by the gathering of contextual qualitative data on service delivery, livelihood opportunities, and the WEF nexus at the town and municipal scales. The results indicated a low-income settlement with a high degree of water and electricity service delivery, which is rare in the South African context. They also revealed a concentration of employment in the fisheries sector, but very little fishing as a means of household food provision. Households typically relied on supermarkets and corner shops for food provision, indicating a reliance on income or financial capital as opposed to other livelihood capitals. All households reported some form of income, with a low percentage relying solely on social grant income. In line with the provisions of The Constitution, households that register as indigent are supported by the municipality in terms of receiving a minimum allocation of free basic water and electricity. The local municipality ensured their financial viability through imposing mechanisms to collect municipal rates debt before they escalated, thus enabling continued provision of basic services to all residents and free basic services to indigent households. The availability of water has been at risk due to recent drought conditions, and this highlighted the significant consumption of the town's largest employer - the large-scale fish processing factory, which through the industrial production of food is also the town's largest electricity consumer. Urgent scaling back of their water consumption was achieved through the installation of a desalination plant, thus averting employment losses through an alternative solution of reducing or stopping factory production. It did however realise other trade-offs, such as an increase in their electricity consumption. The fish factory therefore emerged as a significant actor in the WEF nexus / livelihoods intersection in this case study. Similarly, the local municipality plays a pivotal role in balancing trade-offs between availability and affordability of water and electricity in seeking to foster employment through economic development, as well as the sustainability of basic service provision. The WEF nexus at this level is therefore very useful in highlighting issues of equity, resource status and governance.